2021
DOI: 10.3390/pharmaceutics13111908
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Heat-Assisted Gene Electrotransfer as a Potential Delivery Approach for Protein Replacement Therapy through the Skin

Abstract: Gene-based approaches for protein replacement therapies have the potential to reduce the number of administrations. Our previous work demonstrated that expression could be enhanced and/or the applied voltage reduced by preheating the tissue prior to pulse administration. In the current study, we utilized our 16-pin multi-electrode array (MEA) and incorporated nine optical fibers, connected to an infrared laser, between each set of four electrodes to heat the tissue to 43 °C. For proof of principle, a guinea pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, it was found that moderate tissue preheating before pulse exposure could potentially enhance gene expression while reducing the PEF strength. The minimally invasive electrode array (MEA) with optical fibers for heat production was introduced by the Heller group ( Edelblute et al, 2021 ). The purposed technique was applied on the skin; however, gene expression was also present in deeper layers, including the muscle ( Bulysheva et al, 2019 ).…”
Section: Applications In Vivo and In Clinical Trialsmentioning
confidence: 99%
“…Interestingly, it was found that moderate tissue preheating before pulse exposure could potentially enhance gene expression while reducing the PEF strength. The minimally invasive electrode array (MEA) with optical fibers for heat production was introduced by the Heller group ( Edelblute et al, 2021 ). The purposed technique was applied on the skin; however, gene expression was also present in deeper layers, including the muscle ( Bulysheva et al, 2019 ).…”
Section: Applications In Vivo and In Clinical Trialsmentioning
confidence: 99%
“…However, the application of viral vectors is greatly limited due to limited DNA loading, difficult vector assembly, low efficiency of in vivo introduction, and high costs. Although non-viral vectors such as liposomes, polymer materials, and nano gene transporters have no defects, such as viral toxicity or immunogenicity, their transmission efficiency is very low [ 6 , 7 ]. The active methods for naked DNA transfer include: microinjection, particle bombardment/particle gun, electroporation, and optical methods [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%